Veda as a Source of Dharma Teaching for Character Development in the Globalization - Wika, I Made; Dewi, Ni Luh Putu Yuliani; Pratiwi , Ni Wayan Mita (Dharmakirti : International Journal of Religion, Mind and Science, 2023)
In Hindu teachings, education begins in the womb. However, if it is related to Catur Asrama (the four stages of human life), education begins at the age of 0-25 years to be able to move on to the next level. This study explains that the Vedas are a source of dharma teachings in an effort to develop character in the era of globalization to build a learning mentality and the ability of the learner to be resilient in facing the realities and dynamics of the 21st century. To overcome this problem, as Hindus, we can use the Vedas as a guide for life in facing the current reality. This research was conducted by distributing questionnaires to several samples aged 19-22 years to obtain information and data related to perceptions and whether Vedic learning can influence the development of character in the 21st century. Most of the participants in this study received Vedic learning since entering college and there were some who got it at the elementary, middle, and high school levels and only a few got it through their families. Most of the participants first read Bhagavadgita and Reg Veda which made them feel calm after reading it. This study found that globalization is a technological era that can have a negative influence if it cannot be utilized properly. A dynamic society is trapped in worldly problems. The presence of the Vedas can develop superior human beings with divine character as Veda’s ideals and can develop noble ethics as an effort to face the realities of the 21st century.